2020
DOI: 10.1002/acr.23910
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comorbidity on Physical Function in Patients With Ankylosing Spondylitis and Psoriatic Arthritis Attending Rheumatology Clinics: Results From a Cross‐Sectional Study

Abstract: Objective. To evaluate the impact of comorbidities on physical function in patients with ankylosing spondylitis (AS) and psoriatic arthritis (PsA).Methods. This was a cross-sectional analysis of the baseline visit from the Cardiovascular in Rheumatology study. Multivariate models with physical function as the dependent variable (Bath Ankylosing Spondylitis Functional Index and Health Assessment Questionnaire for AS and PsA, respectively) were performed. Independent variables were a proxy for the Charlson Comor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 14 publications
0
12
1
1
Order By: Relevance
“…These recommendations address non-topical pharmacological treatments with a main focus on musculoskeletal manifestations. As before, the updated recommendations are targeted at various stakeholders, such as (1) experts involved in the care of patients with PsA, particularly rheumatologists and other health professionals (such as rheumatology nurses), but also general practitioners, dermatologists and other specialists; (2) people with PsA who can use these recommendations for information on current therapies, treatment strategies and opportunities; and (3) other stakeholders which include government and hospital officials, patient organisations, regulatory agencies and reimbursement institutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These recommendations address non-topical pharmacological treatments with a main focus on musculoskeletal manifestations. As before, the updated recommendations are targeted at various stakeholders, such as (1) experts involved in the care of patients with PsA, particularly rheumatologists and other health professionals (such as rheumatology nurses), but also general practitioners, dermatologists and other specialists; (2) people with PsA who can use these recommendations for information on current therapies, treatment strategies and opportunities; and (3) other stakeholders which include government and hospital officials, patient organisations, regulatory agencies and reimbursement institutions.…”
Section: Resultsmentioning
confidence: 99%
“…It comprises both musculoskeletal as well as non-musculoskeletal manifestations; the latter particularly include the skin and the nails, but also potentially the gut (inflammatory bowel disease) or the eyes (uveitis). Active chronic PsA also associates with cardiovascular, psychological and metabolic comorbidities, [1][2][3][4][5][6][7] which, together with the musculoskeletal manifestations, impose a significant patient burden with impact on quality of life and also accelerated mortality. [8][9][10] The day-to-day management of patients with PsA includes non-pharmacological as well as pharmacological interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies should avoid using weighted indices that have not been validated for their main outcome of interest (e.g. CCI or ECI for functional impairment [ 21 , 44 ]).…”
Section: Discussionmentioning
confidence: 99%
“…This is not a limitation unique to MarketScan; information regarding disease activity/severity is unlikely to exist in any claims database. We attempted to mitigate the lack of data on disease activity/severity by matching the cohorts based on proxies for potential disease activity/severity, including the Charlson Comorbidity Index (i.e., studies have shown more comorbidity burden is associated with higher disease activity and worse disability/function [23,24]), pre-index cost, prior treatment experience (nonsteroidal anti-inflammatory drugs, steroids, phototherapy) and presence of psoriasis. Residual confounding after the propensity score matching cannot be ruled out; we could only match apremilast-treated patients with biologic-treated patients and could not match apremilast-treated patients with TNFi-treated patients and with ILi-treated patients separately because the sample size for the latter group was too small.…”
Section: Limitationsmentioning
confidence: 99%